PERBANDINGAN EFEKTIVITAS PROMOSI KESEHATAN DENGAN MENGGUNAKAN MEDIA VIDEO DAN BOOKLET TERHADAP KEMAMPUAN SUAMI DALAM MENDUKUNG PERAWATAN BAYI BARU LAHIR - Zulfa, Cahaya Amy; ", Misrawati "; Utami, Gamya Tri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
One of the method to improve the knowledge and the ability of husband in supporting the treatment of  new-born is by using health promotion. This research aimed to compare of health promotion by using video media and booklet toward the ability of husband in supporting the treatment of new born on husband at Sidomulyo inpatient health center area of Pekanbaru. The design of this research was “quasy experiment” by “pre-test and post-test design with two comparison treatments” Sample of this research was 34 respondents based on the inclusive criteria by using technique of purposive sampling. Measuring tool used observation sheet. Data of analysis in this research used univaried analysis to know the distribution of frequency and bivariate analysis to know the dependent T-test and independent T-test. The result of this research indicated 20 persons of respondent had early adult age group (58,8%) 22 persons who had middle education (64,7%) 16 persons were as entreprenuer (47,1%) 11 persons were malay culture (32,4%) 18 persons had 2 childs (52,9%) 32 persons had  normal born weight (94,1%). The result of brivariat analysis indicated that there were differences in ability of husband before and after done the health promotion toward media booklet group and video media by using p value (0,000) < α (0,05) however there were no differences between health promotion using booklet media and health promotion toward  the ability of husband in supporting the baby treatment who were new-born by using p value (0,712) > α (0,05). The research gives advice that using health promotion media shoud be based on the aim group in order to be more effective. Keywords    : The ability, the new-born baby treatment, health promotion, husband.